Aspek Bauran Pemasaran Terhadap Perilaku Konsumen Pengguna Jasa J&T Express Kota Banda Aceh - Marwiyati; Jalilah; Marlinda, Putri (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Changes in consumer lifestyles certainly have a big influence on the growth of online business in Indonesia, this development is the initial sequence for the growth of goods delivery services. One shipping expedition service company that is experiencing development is the J&T Express company. J&T Express helped establish its company in Banda Aceh, to face competition and maintain its credibility the company needs to optimize the implementation of marketing strategies including: brand image, service quality and price. The formulation of the problem and research objectives are to see how brand image, service quality, and price influence consumer decisions in using J&T Express services in Banda Aceh City partially and simultaneously. This research is a quantitative study, using primary data by distributing questionnaires to 153 respondents using a purposive sampling technique. Data analysis used in this research is multiple linear regression analysis. The results of the study show that partially and simultaneously brand image, service quality, and price have a significant effect on the decision to use J&T Express services in Banda Aceh City